Migrationsbedingt behindert? Familien im Hilfesystem : Eine intersektionale Perspektive - Amirpur, Donja (Kultur und soziale Praxis, 2016)
Until now, the category of `culture' functioned as a central category of difference and explanation for reduced ability of the support system to reach families at the intersections of migration and disability. The barriers are alleged to be located above all within the family. Their culturally specific interpretation of disability, according to this assumption, does not correspond to the expectations of empowerment in disability services. To confront this one-dimensional perspective, Donja Amirpur illustrates the complex life situations of these families. Through interviews and with the help of an intersectional, multi-faceted analysis, she depicts the barriers in the support system, and promotes a critical confrontation with hegemonic practices on a structural level.